Assessing Log Reduction Values of Conventional Water Treatment Plants with Microbially Highly Polluted Raw Water Sources - Arief Sudradjat; Made Sandhyana Angga; Kevin Barlian; Anindrya Nastiti (Directorate for Research and Community Services, Institut Teknologi Bandung, 2022)
Because of the global outlook of microbial pathogens contributed by river basins that are characterized by highly populated urbanized areas and other activities with poor wastewater management, it is imperative to assess the sufficiency of conventional water treatment plants with microbially highly polluted raw surface water sources in supplying pathogen-free drinking water. By using the log reduction value (LRV), the microbial safety of the drinking water supply from WTP Badaksinga, Bandung City, Indonesia, was assessed, from the raw water sources to the conventional water treatment units. E. coli, total coliform, and Clostridium perfringens (as a surrogate of the Cryptosporidium parvum protozoan) were selected as pathogens. It was found that with E. coli concentrations of > 20,000 MPN/100 ml, all the raw water sources should be categorized as not suitable for drinking water sources. The LRVs of conventional treatment units ranged from 0.67 to 1.4 for all pathogens. For the disinfection unit, the LRVs ranged from 3.0 to 3.71 for E. coli and total coliform, and 0 for Clostridium perfringens. Based on the results, the drinking water from WTP Badaksinga is safe from bacteria contamination but theoretically requires an additional barrier for protozoa safety. The assessment found that the LRVs of pre-sedimentation and combined flocculation-sedimentation units in conventional treatment systems need to be (re)assessed.